Use of caliper-based external measurement of body surface in assessing the severity of pectus excavatum - Chen, Tian; Chen, Chenghao; Zeng, Qi; Zhang, Yan; Jiao, Jinghua; Zhang, Xu; Zhang, Na; Yu, Jie (Frontiers in Pediatrics, 2022)
Introduction: Objective assessment of the severity of pectus excavatum (PE) mainly depends on internal imaging examination, which poses radiation exposure risks and high financial costs. Our study explores the feasibility of caliper-based external measurements of the body surface to assess PE severity. Materials and Methods: Patients with PE aged 4-18 years who underwent both internal imaging examinations and external measurements were chosen for the study. Overall, 176 patients underwent surgery and 21 underwent regular observation. The Haller index (HI) and correction index (CI) were used to derive the external measurement indices, HI-caliper and CI-caliper. Receiver-operator characteristic analysis provided the optimal cut-off values and compared the diagnostic values of HI-caliper and CI-caliper. Spearman's correlation coefficient and Cohen's kappa coefficient were used to analyze the correlation and consistency between HI-caliper or CI-caliper and HI-CT or CI-CT, respectively. Also, a paired samples t-test was used to compare the differences of HI-caliper or CI-caliper before and after surgery. Results: HI-caliper and CI-caliper measurements had strong correlations with HI-CT and CI-CT results (rs=0.70, p<0.001; rs=0.69, p<0.001), respectively. The optimal cut-off values of HI-caliper and CI-caliper were 1.83 (sensitivity=0.841, specificity=0.905) and 12% (sensitivity=0.881, specificity=0.857), exhibiting comparable diagnostic values with HI-CT and CI-CT. HI-caliper>1.83 or CI-caliper>12% had medium intensity consistency with HI-CT≥3.25 or CI-CT≥28% (k=0.545, 95% confidence interval: 0.374-0.716, p<0.001). The HI-caliper and CI-caliper values were significantly different before and after surgery. Conclusions: Caliper-based external measurement is a feasible method to screen patients who require surgical intervention and for monitoring the progression of PE severity.